Recyclable induced crystallization agent, preparation method and application thereof

CN120364897BActive Publication Date: 2026-10-27KUNMING METALLURGY INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510579943.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-07
Publication Date
2026-10-27
Estimated Expiration
2045-05-07

AI Technical Summary

Technical Problem

结垢会阻碍离子在电极表面的传递和反应,降低电解效率,增加能耗,并且需要定期对电极进行清洗,影响设备的连续运行,因此开发一种能解决上述技术问题的产品以及方法具有重要意义

Benefits of technology

1.通过阴极结构设计及可循环利用的诱导结晶剂协同,克服了传统电化学除硬方法阴极表面结垢难去除的困难,有效提升阴极寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120364897B_ABST
    Figure CN120364897B_ABST
Patent Text Reader

Abstract

The application provides a recyclable induced crystallization agent and a preparation method and application thereof. The recyclable induced crystallization agent is composed of a water-soluble binder, a thickening agent, Fe3O4 powder, activated carbon powder and induced crystallization material powder. The application overcomes the difficulty of removing the scale on the surface of a cathode in a traditional electrochemical hardness removal method by the cooperation of a cathode structure design and the recyclable induced crystallization agent, and effectively improves the service life of the cathode. The electrolytic tank discharge residue is linked with a magnetic separation system and an electric flocculation-cyclone centrifugal system, the solid-liquid separation efficiency is high, and the system can be continuously operated for a long time. The generated precipitate can be recycled, and resources are saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metallurgy and chemical engineering, specifically relating to a recyclable inducing crystallizer, its preparation method, and its application. Background Technology

[0002] Electrochemical hardness removal technology is a common industrial wastewater treatment technology for high-hardness wastewater, offering advantages such as fast treatment speed, no secondary pollution, and simple operation. However, with long-term use, scale formation occurs on the cathode surface due to the precipitation of hardness ions, resulting in deposits such as calcium carbonate and magnesium hydroxide. Scale formation hinders ion transport and reaction on the electrode surface, reducing electrolysis efficiency, increasing energy consumption, and requiring regular electrode cleaning, thus affecting the continuous operation of the equipment. Therefore, developing a product and method to solve these technical problems is of great significance. Summary of the Invention

[0003] The first objective of this invention is to provide a recyclable crystallizing agent; the second objective is to provide a method for preparing the recyclable crystallizing agent; and the third objective is to provide applications of the recyclable crystallizing agent.

[0004] The first objective of this invention is achieved by the recyclable crystallizing agent comprising a water-soluble binder, a thickener, Fe3O4 powder, activated carbon powder, and crystallizing material powder.

[0005] The second objective of this invention is achieved by including pretreatment, binding matrix preparation, and formulation steps, specifically including: A. Pretreatment: The Fe3O4 powder, activated carbon powder and crystallization-inducing material powder in the formula are mixed and then ball-milled through a 400-mesh sieve to obtain material a; B. Preparation of the adhesive substrate: 1) Mix the water-soluble binder and thickener according to the formula to obtain material b; 2) Under high-speed stirring conditions of 10,000~12,000 r / min, dissolve material b in 10~15 times its mass of deionized water and stir for 15~25 min to obtain colloidal matrix c; C. Preparation: Under high-speed stirring conditions of 10000~12000r / min, material a is added to colloidal matrix c and stirring is continued for 10~30min to obtain induced crystallization slurry, which is the induced crystallizer that can be recycled for the target material.

[0006] The third objective of this invention is achieved as follows: the application of the recyclable inducing crystallizer in an electrochemical hardening system with self-cleaning function, specifically in the following operation mode: Phase 1 (Preparation of Induced Crystallization Slurry): The induced crystallization slurry (hereinafter referred to as slurry) is made by mechanically mixing deionized water, water-soluble binder, thickener, Fe3O4 powder, activated carbon powder, and induced crystallization material powder.

[0007] Stage 2 (Slurry Injection): The slurry supply system injects slurry into the cathode cavity of the electrochemical hardening device at a certain pressure, forming protrusions at the micropores on the cathode surface and flowing out at a certain speed.

[0008] Stage 3 (Electrolytic Dehardening): Current is applied, and water is electrolyzed on the cathode surface and slurry surface. Under the action of the inducing crystallization material, Ca... 2+ / Mg 2+ Scaling occurs on raised surfaces.

[0009] Stage 4 (Scale Shedding): As the slurry flows out and the surface scale increases, the binder gradually dissolves, causing the slurry strength to decrease. Under the action of gravity and the flushing of water flow, the slurry and scale detach from the cathode surface, achieving the purpose of self-cleaning.

[0010] Stage 5 (Sedimentation Separation): Larger particles accumulate at the bottom of the electrochemical hardening system and are discharged through the slag outlet. The magnetic separation system separates the magnetic micro-precipitates, and the inclined tube sedimentation tank further separates the non-magnetic micro-precipitates. The wastewater separated by sedimentation is discharged from the effluent pipe.

[0011] Phase 6 (Sediment Utilization): Large particles and magnetic sediments can be dried, ground, and sieved before being recycled as raw materials for slurry.

[0012] The mechanism of action of the recyclable crystallizing agent described in this invention is as follows: The recyclable crystallizing agent is composed of deionized water, a water-soluble binder, a thickener, Fe3O4 powder, activated carbon powder, and crystallizing material powder, which are mechanically mixed. The water-soluble binder gives the slurry a certain degree of water solubility and viscosity. The thickener further enhances the viscosity of the slurry, allowing it to maintain a certain strength under the scouring of water flow. The Fe3O4 powder gives the slurry magnetic and conductive properties. The crystallizing material powder causes scale to tend to form on the surface of the slurry, preventing scale formation on the cathode surface. The activated carbon powder further enhances the conductivity and crystallization induction performance of the slurry and can adsorb some other pollutants (heavy metals, organic matter, etc.) in the wastewater. During the hardening process, as the slurry flows out continuously, scale gradually forms on the surface of the slurry. At the same time, the gradual dissolution of the water-soluble binder and thickener causes the strength of the mixed slurry to gradually decrease. Finally, under the action of gravity and the scouring of water flow, the mixed slurry and surface scale fall off on their own, achieving the purpose of self-cleaning. Since the detached precipitate contains induced crystallization slurry and the resulting scale can be used as induced crystallization material, it can be recycled as raw material for induced crystallization slurry through treatment.

[0013] Advantages of this invention: 1. By designing the cathode structure and using a recyclable inducing crystallizer, the difficulty of removing scale from the cathode surface by traditional electrochemical hardening methods is overcome, effectively improving the cathode lifespan.

[0014] 2. The electrolytic cell slag discharge system is linked with the magnetic separation system and the electrocoagulation-cyclone centrifugation system, resulting in high solid-liquid separation efficiency and allowing the system to operate continuously for extended periods.

[0015] 3. The resulting sediment can be recycled, saving resources. Attached Figure Description

[0016] Figure 1 This is a schematic diagram of the electrochemical hardening device of the present invention; Figure 2 This is a schematic diagram of the electrochemical hardening system with self-cleaning function of the present invention; Figure 3 This is a schematic diagram of the cathode plate structure of the present invention; In the diagram, 1-Electrochemical hardening removal device, 2-Magnetic separation system, 3-Cyclone centrifuge, 4-Electrocoagulation system, 5-Material recovery system, 6-Electrolytic cell, 7-Inlet pipe, 8-Outlet pipe, 9-Induced crystallization slurry, 10-Outlet pipe, 11-Intelligent CO2 replenishment system, 12-Anode plate, 13-Cathode plate, 14-Electrode power supply, 15-Slag discharge port, 16-Micropores, 17-Storage silo, 18-Constant pressure pump, 19-Intelligent pressure control system, 20-Control cabinet I, 21-Online hardness monitor, 22-Online pH monitor, 23-Control cabinet II, 24-Slurry supply system. Detailed Implementation

[0017] The present invention will be further described below with reference to embodiments, but this is not intended to limit the present invention in any way. Any modifications or substitutions made based on the teachings of the present invention shall fall within the protection scope of the present invention.

[0018] The recyclable crystallizing agent described in this invention is composed of a water-soluble binder, a thickener, Fe3O4 powder, activated carbon powder, and crystallizing material powder.

[0019] The mass ratio of the water-soluble binder, thickener, Fe3O4 powder, activated carbon powder and induced crystallization material powder is (4~6):(0.4~0.6):(8~12):(4~6):(10~20).

[0020] The water-soluble binder is carboxymethyl cellulose.

[0021] The thickener is xanthan gum.

[0022] The material used to induce crystallization is calcium carbonate.

[0023] The method for preparing the recyclable crystallizing agent of the present invention includes pretreatment, preparation of colloidal matrix and formulation steps, specifically including: A. Pretreatment: The Fe3O4 powder, activated carbon powder and crystallization-inducing material powder in the formula are mixed and then ball-milled through a 400-mesh sieve to obtain material a; B. Preparation of the adhesive substrate: 1) Mix the water-soluble binder and thickener according to the formula to obtain material b; 2) Under high-speed stirring conditions of 10,000~12,000 r / min, dissolve material b in 10~15 times its mass of deionized water and stir for 15~25 min to obtain colloidal matrix c; C. Preparation: Under high-speed stirring conditions of 10000~12000r / min, material a is added to colloidal matrix c and stirring is continued for 10~30min to obtain induced crystallization slurry, which is the induced crystallizer that can be recycled for the target material.

[0024] The application of this invention is the use of the recyclable inducing crystallizer in an electrochemical hardening system with self-cleaning function.

[0025] The self-cleaning electrochemical hardening system includes an electrochemical hardening device 1, a magnetic separation system 2, a cyclone centrifuge 3, an electrocoagulation system 4, and a material recovery system 5. The electrochemical hardening device 1, magnetic separation system 2, cyclone centrifuge 3, and electrocoagulation system 4 are connected sequentially. Both the electrochemical hardening device 1 and the magnetic separation system 2 are connected to the material recovery system 5. The electrocoagulation system 4 is connected to an outlet pipe 10. The electrochemical hardening device 1 includes an electrolytic cell 6, which includes an anode plate 12, a cathode plate 13, and an electrode power supply 14. The cathode plate 13 is a copper-nickel alloy electrode plate or a stainless steel electrode plate, and the anode plate 12 is a titanium-based coated anode plate. The anode plate 12 and the cathode plate 13 are respectively connected to the positive and negative terminals of the power supply. When current is applied, water is electrolyzed on the cathode surface and the surface of the induced crystallization slurry 9. Under the action of the induced crystallization slurry 9 (hereinafter referred to as the slurry), Ca... 2+ / Mg 2+Scaling occurs on the raised surface; the cathode plate 13 is connected to the slurry supply system 24 via a pipeline. The cathode plate 13 is a hollow porous cathode plate, which is hollow inside and has micropores 16 evenly distributed on its surface. The diameter of the micropores 16 is 0.1mm~1mm, and the diameter of the micropores 16 increases from top to bottom. This arrangement allows the slurry inside the cathode plate 13 to flow out smoothly, avoiding slurry accumulation and blockage; the bottom of the electrolytic cell 6 is provided with a slag discharge port 15, which is conical in shape and is connected to the material recovery system 5 via a pipeline; the electrolytic cell The upper and lower sides of the 6 are respectively connected to the outlet pipe 8 and the inlet pipe 7. The outlet pipe 8 is connected to the magnetic separation system 2, and the inlet pipe 7 is connected to the CO2 intelligent replenishment system 11. Larger particles accumulate at the bottom of the electrochemical hardening device 1 and are discharged through the slag discharge port 15. The magnetic separation system 2 separates the magnetic micro-precipitates. The cyclone centrifuge 3 and the electrocoagulation system 4 quickly separate the non-magnetic micro-precipitates. The wastewater separated by sedimentation is discharged from the outlet pipe 10. Large particles and magnetic precipitates are dried, ground, and screened by the material recovery system 5 and then recycled as raw materials for the induced crystallization slurry 9.

[0026] The slurry supply system 24 includes a storage bin 17 and a constant pressure pump 18. The storage bin 17 is filled with an induced crystallization slurry 9, which is made by mechanically mixing deionized water, water-soluble binder, thickener, Fe3O4 powder, activated carbon powder, and induced crystallization material powder. The slurry supply system 24 injects the slurry into the cathode plate 13 cavity of the electrochemical hardening device 1 at a certain pressure, forming a protrusion at the micropores 16 on the cathode surface and flowing out at a certain speed.

[0027] The electrochemical hardening device 1 is also connected to an intelligent pressure control system 19. The intelligent pressure control system 19 includes a control cabinet I 20 and an online hardness monitor 21. The constant pressure pump 18 is installed on the pipeline connecting the slurry supply system 24 and the cathode plate 13. The online hardness monitor 21 is installed on the water inlet pipe 7 and transmits signals with the control cabinet I 20. The online hardness monitor 21 monitors the hardness of the inlet water in real time and feeds it back to the control cabinet I. The control cabinet I dynamically adjusts the pressure of the constant pressure pump 18 to control the slurry outflow rate.

[0028] The intelligent CO2 replenishment system 11 includes a control cabinet II 23 and an online pH monitor 22. The online pH monitor 22 is installed inside the electrolytic cell 6 and is electrically connected to the control cabinet II 23. The control cabinet II 23 is connected to the inlet pipe 7. The online pH monitor 22 monitors the pH of the effluent in real time and feeds it back to the control cabinet II 23. The control cabinet II 23 dynamically adjusts the CO2 injection rate through the inlet pipe 7 to maintain HCO32 in the cathode area. - / CO3 2- balance.

[0029] Working principle First, the slurry supply system 24 injects slurry into the hollow cavity of the cathode plate 13 of the electrochemical hardening device 1 at a certain pressure, forming protrusions at the micropores 16 on the surface of the cathode plate 13 and flowing out at a certain speed; then, an electric current is applied, and water is electrolyzed on the surface of the cathode plate 13 and the surface of the slurry. Under the action of the inducing crystallization material, Ca... 2+ / Mg 2+ Scaling occurs on the raised surface; as the slurry flows out and the surface scaling increases, the binder gradually dissolves, causing the slurry strength to decrease. Under the action of gravity and the flushing of water flow, the slurry and scaling fall off the surface of the cathode plate 13, achieving the purpose of self-cleaning; larger particles accumulate at the bottom of the electrochemical hardening device 1 and are discharged through the slag discharge port 15. The magnetic separation system 2 separates the magnetic micro-precipitates, and the cyclone centrifuge 3 and the electrocoagulation system 4 quickly separate the non-magnetic micro-precipitates. The wastewater separated by sedimentation is discharged from the effluent pipe 10; large particles and magnetic precipitates are dried, ground, and screened by the material recovery system 5 and then recycled as raw materials for the induced crystallization slurry 9.

[0030] It should be noted that the induced crystallization slurry 9 is composed of deionized water, water-soluble binder, thickener, Fe3O4 powder, activated carbon powder, and induced crystallization material powder, which are mechanically mixed. The water-soluble binder gives the slurry a certain degree of water solubility and viscosity, while the thickener further enhances the viscosity, allowing it to maintain a certain strength under the scouring of water flow. The Fe3O4 powder gives the slurry magnetic and electrical properties, and the induced crystallization material powder causes scaling to tend to form on the surface of the slurry, preventing scaling on the cathode plate 13. The activated carbon powder further enhances the conductivity of the slurry. It possesses electrical properties and induces crystallization, and can adsorb some other pollutants in wastewater, such as heavy metals and organic matter. During the hardening process, under the action of pressure, water flow, and gravity, the slurry maintains a parallel and continuous flow, and scale gradually forms on the surface of the slurry. At the same time, the gradual dissolution of water-soluble binders and thickeners causes the strength of the mixed slurry to gradually decrease. Finally, under the action of gravity and the scouring of water flow, the mixed slurry and surface scale fall off on their own, achieving the purpose of self-cleaning. Simultaneously, water flows in from the lower part of the cathode plate 13 and flows out from the upper part. Driven by the water flow, it can prevent the generation of OH in the cathode. - Diffusion towards the anode improves hardening efficiency; since the detached precipitate contains induced crystallization slurry 9, and the generated scale can be used as induced crystallization material, it can be recycled as raw material for induced crystallization slurry 9 through treatment.

[0031] The invention will be further illustrated below with specific implementation examples: Example 1

[0032] Composition: Deionized water (60%), water-soluble binder (carboxymethyl cellulose, 5%), thickener (xanthan gum, 0.5%), Fe3O4 powder (10%), activated carbon powder (5%), and crystallizing material (CaCO3 powder, 15%), in percentages by mass.

[0033] Process: (1) Add 10g Fe3O4 powder, 5g activated carbon powder and 15g calcium carbonate powder to a ball mill and ball mill for 1.5h. After ball milling, pass through a 400-mesh sieve to obtain mixed powder.

[0034] (2) Under the condition of 11000 r / min speed of high speed mixer, 5g carboxymethyl cellulose and 0.5g xanthan gum are dissolved in 60g deionized water at 50℃ and stirred for 20min to form a gel matrix.

[0035] (3) Under the condition of 11000 r / min speed of high speed mixer, the mixed powder of step (1) is slowly added to the colloidal matrix of step (2) and stirred for 20 min to form induced crystallization slurry, that is, the induced crystallizer that can be recycled for the target material.

[0036] Example 2

[0037] Composition: Deionized water (70%), water-soluble binder (carboxymethyl cellulose, 4%), thickener (xanthan gum, 0.4%), Fe3O4 powder (8%), activated carbon powder (4%), and crystallizing material (CaCO3 powder, 13.6%), in percentage by mass.

[0038] Process: (1) Add 8g Fe3O4 powder, 4g activated carbon powder and 13.6g calcium carbonate powder to a ball mill and ball mill for 2 hours. After ball milling, pass through a 400-mesh sieve to obtain mixed powder.

[0039] (2) Under the condition of 12000 r / min speed of high speed mixer, 4g carboxymethyl cellulose and 0.4g xanthan gum were dissolved in 70g deionized water at 55℃ and stirred for 12min to form a gel matrix.

[0040] (3) Under the condition of 12000 r / min speed of high speed mixer, the mixed powder of step (1) is slowly added to the colloidal matrix of step (2) and stirred for 30 min to form induced crystallization slurry, that is, the induced crystallizer that can be recycled for the target material.

[0041] Example 3

[0042] Components: Deionized water (58%), water-soluble binder (carboxymethyl cellulose, 6%), thickener (xanthan gum, 0.6%), Fe3O4 powder (12%), activated carbon powder (6%), and crystallizing material (CaCO3 powder, 17.4%), in percentage by mass.

[0043] Process: (1) Add 12g Fe3O4 powder, 6g activated carbon powder and 17.4g calcium carbonate powder to a ball mill and ball mill for 1.8h. After ball milling, pass through a 400-mesh sieve to obtain mixed powder.

[0044] (2) Under the condition of 10,000 r / min speed of high speed mixer, 6g carboxymethyl cellulose and 0.6g xanthan gum were dissolved in 58g deionized water at 45℃ and stirred for 30min to form a gel matrix.

[0045] (3) Under the condition of 10,000 r / min speed of high speed mixer, the mixed powder of step (1) is slowly added to the colloidal matrix of step (2), and the mixture is stirred for 30 min to form an induced crystallization slurry, which is the induced crystallizer that can be recycled.

[0046] Example 4

[0047] The recyclable crystallizing agent prepared in Example 1 was used in the experiment, and the results are as follows: The total hardness of the circulating cooling water of a certain enterprise is about 600 mg / L. The electrochemical hardness removal device and system of the present invention are used for treatment. The slurry used is prepared according to Example 1. The equipment operating parameters are shown in Table 1. After 5 months of continuous operation, the hardness of the effluent at each time point is shown in Table 2.

[0048] Table 1 Equipment Operating Parameters

[0049] Table 2. Changes in effluent hardness at different time points

[0050] Example 5

[0051] The recyclable crystallizing agents prepared in Examples 2 and 3 were tested respectively, using the same method as in Example 4. The results showed that the present invention has the advantages of high efficiency and long cycle operation, and is suitable for large-scale treatment of industrial high hardness wastewater.

Claims

1. The application of a recyclable inducing crystallizer in an electrochemical hardening system with self-cleaning function, characterized in that, The recyclable crystallizing agent is composed of deionized water, water-soluble binder, thickener, Fe3O4 powder, activated carbon powder, and calcium carbonate powder as the crystallizing agent. The self-cleaning electrochemical hardening system includes an electrochemical hardening device (1), a magnetic separation system (2), a cyclone centrifuge (3), an electrocoagulation system (4), and a material recovery system (5). The electrochemical hardening device (1), the magnetic separation system (2), the cyclone centrifuge (3), and the electrocoagulation system (4) are connected in sequence. The electrochemical hardening device (1) and the magnetic separation system (2) are both connected to the material recovery system (5). The electrocoagulation system (4) is connected to an outlet pipe (10). The electrochemical hardening device (1) includes an electrolytic cell (6), which is connected to a slurry supply system (24). The electrolytic cell (6) includes an anode plate (12) and a cathode plate (13). The cathode plate (13) is a hollow porous cathode plate. The hollow porous cathode plate is hollow inside and has micropores (16) evenly distributed on its surface. The slurry supply system (24) injects slurry into the cathode plate (13) cavity of the electrochemical hardening device (1) at a certain pressure, forming a protrusion at the micropore (16) on the cathode surface and flowing out at a certain speed.

2. The application of the recyclable inducing crystallizer according to claim 1 in an electrochemical hardening system with self-cleaning function, characterized in that, The mass ratio of the water-soluble binder, thickener, Fe3O4 powder, activated carbon powder and calcium carbonate powder (the inducing crystallization material) is (4~6):(0.4~0.6):(8~12):(4~6):(10~20).

3. The application of the recyclable inducing crystallizer according to claim 1 or 2 in an electrochemical hardening system with self-cleaning function, characterized in that, The water-soluble binder is carboxymethyl cellulose.

4. The application of the recyclable inducing crystallizer according to claim 1 or 2 in an electrochemical hardening system with self-cleaning function, characterized in that, The thickener is xanthan gum.

5. The application of the recyclable inducing crystallizer according to claim 1 or 2 in an electrochemical hardening system with self-cleaning function, characterized in that, The method for preparing the crystallizing agent includes pretreatment, preparation of the colloidal matrix, and formulation steps, specifically including: A. Pretreatment: Fe3O4 powder, activated carbon powder and calcium carbonate powder (inducing crystallization material) are mixed according to the formula and then ball-milled through a 400-mesh sieve to obtain material a; B. Preparation of colloidal matrix: 1) Mix the water-soluble binder and thickener according to the formula to obtain material b; 2) Under high-speed stirring conditions of 10,000~12,000 r / min, dissolve material b in 10~15 times its mass of deionized water and stir for 15~25 min to obtain colloidal matrix c; C. Preparation: Under high-speed stirring conditions of 10000~12000r / min, material a is added to colloidal matrix c and stirring is continued for 10~30min to obtain induced crystallization slurry, which is the induced crystallizer that can be recycled for the target material.

6. The application of the recyclable inducing crystallizer according to claim 1 in an electrochemical hardening system with self-cleaning function, characterized in that, The electrolytic cell (6) is equipped with an inlet pipe (7) and an outlet pipe (8), and the inlet pipe (7) is connected to a CO2 intelligent replenishment system (11).

Citation Information

Patent Citations

  • Electrochemical sewage treatment system for relieving cathode scaling and application thereof

    CN116495900A

  • Water softening device, and water softening method

    JP2020121238A